Synchronous Diagnosis of Multiple Myeloma, Breast Cancer, and Monoclonal B-Cell Lymphocytosis on Initial Presentation. (10th May 2016) - Vennepureddy, A.; Motilal Nehru, V.; Liu, Y.; Mohammad, F.; Atallah, J. P.
Abstract : The cooccurrence of more than one oncologic illness in a patient can present a diagnostic challenge. Here we report an unusual case of concomitant existence of multiple myeloma, breast cancer, and monoclonal B-cell lymphocytosis on initial presentation. The challenge was to accurately diagnose each disease and stage in order to maximize the therapeutic regimen to achieve cure/remission. Successful management of the patient and increased life expectancy can be achieved by multidisciplinary management and patient-oriented approach in multiple primary malignant synchronous tumors.